2013
DOI: 10.1136/jnnp-2012-304270
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of neurodevelopmental disorders in children prenatally exposed to antiepileptic drugs

Abstract: The aim of this study was to compare the prevalence of diagnosed neurodevelopmental disorders in children exposed, in utero, to different antiepileptic drug (AED) treatments. A prospective cohort of women with epilepsy and a control group of women without epilepsy were recruited from antenatal clinics. The children of this cohort were followed longitudinally until six years of age (n=415). Diagnosis of a neurodevelopmental disorder was made independently of the research team. Multiple logistic regression analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
235
4
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 318 publications
(250 citation statements)
references
References 44 publications
(37 reference statements)
7
235
4
4
Order By: Relevance
“…The neurodevelopment research group from Liverpool and Manchester also reported that children assessed at 6 years of age who were exposed to VPA in utero had a higher prevalence of neurodevelopmental disorders [22]. Multiple logistic regression analysis revealed that the children born to WWE and exposed to VPA monotherapy and VPA polytherapy were, respectively, 6 times [adjusted OR 6.05; 95 % CI 1.65-24.53 (p = 0.007)] and 10 times [adjusted OR 9.97; 95 % CI 1.82-49.40 (p = 0.005)] more likely to be diagnosed with a neurodevelopmental disorder than controls.…”
Section: Neurodevelopmental Outcomesmentioning
confidence: 99%
“…The neurodevelopment research group from Liverpool and Manchester also reported that children assessed at 6 years of age who were exposed to VPA in utero had a higher prevalence of neurodevelopmental disorders [22]. Multiple logistic regression analysis revealed that the children born to WWE and exposed to VPA monotherapy and VPA polytherapy were, respectively, 6 times [adjusted OR 6.05; 95 % CI 1.65-24.53 (p = 0.007)] and 10 times [adjusted OR 9.97; 95 % CI 1.82-49.40 (p = 0.005)] more likely to be diagnosed with a neurodevelopmental disorder than controls.…”
Section: Neurodevelopmental Outcomesmentioning
confidence: 99%
“…For example, Ͼ40 different mutations and various environmental risk factors have been associated with ASD (Abrahams and Geschwind, 2008;Lichtenstein et al, 2010;Neale et al, 2012). Despite this great diversity of potential causes and complex cognitive symptoms, there is reason to believe that these symptoms originate from a few fundamental abnormalities in nervous system development and function (Pratt and Khakhalin, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Earlier publications from this longitudinal cohort have reported an increased risk of major congenital malformations, 19 significantly lower early cognitive development, 15 and increased rates of autistic spectrum disorder 20 after exposure to VPA.…”
mentioning
confidence: 99%